Carnosine content in the porcine longissimus thoracis muscle and its association with meat quality attributes and carnosine-related gene expression. (February 2017) - D'Astous-Pagé, Joël; Gariépy, Claude; Blouin, Richard; Cliche, Simon; Sullivan, Brian; Fortin, Frédéric; Palin, Marie-France
Abstract: Muscle carnosine has pH-buffering, antioxidant and carbonyl scavenging properties, which may affect pork quality attributes. Study objectives were to: (1) compare muscle carnosine content and carnosine-related gene mRNA abundance in purebred pigs (n = 282), (2) study the effect of muscle carnosine content on pork quality attributes and gene expression across breeds, and (3) study transcript abundance of carnosine-related genes in various tissues. Pigs were raised under similar conditions and slaughtered at 120 ± 4.5 kg. Longissimus thoracis muscles were sampled on the dressing line for gene expression and at 24 h for meat quality measurements. Muscle carnosine content and carnosine-related gene mRNA abundance were modulated according to pig breeds. Greater pH 24 h, better water holding capacity and improved meat color values were found in pigs with high muscle carnosine content. Data suggest that high muscle carnosine is associated with improved pork meat quality attributes. The pig genetic background may be a key determinant for muscle carnosine content regulation.